Performance Measurement of Interlibrary Loan for University Libraries in Taiwan in the Digital Age - Mei-Ling, Wang; Yang, Chieh (Qualitative and Quantitative Methods in Libraries, 2019)
The study mainly discusses performance measurements of interlibrary loan for university libraries in Taiwan. The purposes of the study are: 1) to explore the status of interlibrary loan services for university libraries in Taiwan; 2) to investigate the effect of electronic resources on interlibrary loan services; 3) to collect and analyze current data on the performance of ILL services of university libraries; 4) to identify and describe characteristics of low-cost, high-performing ILL operations. The study used questionnaire surveys and performance evaluation method with four performance measures to evaluate borrowing and lending services: cost, fill rate, turnaround time, and collection sufficiency. In 2014, the researcher sent questionnaires to 169 university libraries to collect the interlibrary loan operations and performance data in 2013. The study found electronic resources had influenced ILL services, and that 29 participants (27.1%) provided database ILL services, 28 participants provided e-journals ILL (26.2%), 5 participants (4.7%) provided e-book ILL services. With the implementation the NDDS ILL information system in 2013, the ILL service performance of 107 participants were assessed, the average ILL transaction per library was 993, the average ILL borrowing transaction per library was 484, and the average ILL lending transaction per library was 509. The borrowing unit cost was NT$165, and the lending unit cost was NT$129. The borrowing fill rate was 79%, and the lending fill rate was 82%. The borrowing turnaround time was 1.98 days, and the lending turnaround time was 1.54 days. As the ratio of requests received to requests sent out in interlibrary lending was 1.1, it showed that the collection of university libraries was sufficient and adequate. This study carried out a performance measurement of ILL service, constructed four performance measures and described the performance of ILL service for university libraries in Taiwan as costing less with a faster turnaround time, higher fill rate and a sufficient and adequate collection. The study is valuable because it proposed new performance measures and significant findings of effects of e-resources in interlibrary loan services.